2017
DOI: 10.1002/adfm.201703934
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis‐Responsive Thrombolytic Coating Based on Thrombin‐Degradable Tissue Plasminogen Activator (t‐PA) Nanocapsules

Abstract: Surface modification with bioactive agents capable of combating thrombosis is a widely used strategy for developing antithrombotic biomaterials. However, exposure of the blood to the antithrombotic agent on the material surface may cause hemostatic disorders under normal conditions. Ideally an implanted biomaterial should respond appropriately on demand to a specific change in the physiologic environment, as happens in the body itself. In the present study, a thrombosis-responsive surface coating with the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…In addition, the tails of HDP‐treated mice exhibit the similar structure as the normal mice with purple and blue structure dominantly; confirming that pretreatment with HDP‐2 and HDP‐4 nanoparticles restrains the clot formation effectively (Figure e,f). In addition, there is nearly no histological evidence of accumulated toxicity in the different organs after administration of nanoparticles for 3 days (Figure S8, Supporting Information), demonstrating the excellent biocompatibility of HDP nanoparticles . Taken together, we confirmed that the prepared HDP nanoparticles can be employed to treat thrombus associated with inflammation without lethal side effects on hemostasis.…”
Section: Resultssupporting
confidence: 58%
“…In addition, the tails of HDP‐treated mice exhibit the similar structure as the normal mice with purple and blue structure dominantly; confirming that pretreatment with HDP‐2 and HDP‐4 nanoparticles restrains the clot formation effectively (Figure e,f). In addition, there is nearly no histological evidence of accumulated toxicity in the different organs after administration of nanoparticles for 3 days (Figure S8, Supporting Information), demonstrating the excellent biocompatibility of HDP nanoparticles . Taken together, we confirmed that the prepared HDP nanoparticles can be employed to treat thrombus associated with inflammation without lethal side effects on hemostasis.…”
Section: Resultssupporting
confidence: 58%
“…Entrapped enzyme activity was assayed using a colourimetric method based on S‐2251 substrates [46, 47]. Substrate solution was prepared briefly by adding 1 ml Tris (0.5 M, pH = 7.4) and 5 μl Tween‐20 to 1 ml of 3 mM S‐2251.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, Chen et al developed a thrombosis-responsive surface coating with the ability to lyse fibrin as it forms. 466,467 Thrombin generation is a key event in blood coagulation/thrombosis and therefore has been used as a physiologic stimulus or trigger in the design of this coating. As shown in Fig.…”
Section: Interactions Of Biomaterials Surfaces/interfacesmentioning
confidence: 99%